2021
DOI: 10.3390/medicina57101092
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Efficiency and Prognostic Value of the Sentinel Node Technique in Oral Squamous Cell Carcinoma after Seven Years

Abstract: Background and objectives: The purpose of this study was to analyse the diagnostic and prognostic efficiency of the sentinel lymph node biopsy technique (SLNB). Materials and Methods: This is a prospective observational study performed by the Hospital Complex in Santiago de Compostela (CHUS) in Spain, between February 2013 and June 2020. The study included 60 patients, who had been diagnosed with OSCC in stage T1/T2N0M0. Results: 10 patients (16.7%) presented with SN+ (sentinel node positive). The majority (80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…This is particularly relevant, as multiple studies have demonstrated worse overall survival for patients with SLN+ disease, with rates as low as 38%, in comparison with overall survival rates of more than 80% for patients with SLN− disease. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant, as multiple studies have demonstrated worse overall survival for patients with SLN+ disease, with rates as low as 38%, in comparison with overall survival rates of more than 80% for patients with SLN− disease. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…Staging was performed according to the 8th edition of the American Joint Committee on Cancer's Cancer Staging Manual. The established protocol of the University Hospital of Santiago de Compostela (Santiago de Compostela, Corunna, Spain) was followed [41,42]. The decision to perform surgery was made by the maxillofacial surgeon based on a comprehensive examination and deliberation by the CHUS committee for tumors.…”
Section: Patient Selection and Clinical Datamentioning
confidence: 99%